Evaluación del efecto de la concentración de CsI sobre la morfología de Perovskitas bicatión CsX(MA1-X)Pb(I)3 sintetizadas para el uso como capa activa en celdas solares fotovoltaicas (2018)
In this work, thin films of perovskite of mixed cation CsxMA1-xPbI3 were synthesized by means of the spin coating deposition technique to be used as absorptive layers in photovoltaic solar cells. The effect of the CsI concentration on the optical and morphological properties of CsxMA1-xPbI3 films was evaluated and a regular morphological evolution was observed. Through reflectance and diffuse transmittance measurements, the synthesis parameters were found that ensure good properties for the materials in terms of energy gap, film thickness and photonic absorption coefficient. From the measurements of AFM, the growth of compact grains of submicrometric size of CsxMA1-xPbI3 was evidenced. It is suggested that the incorporation of a quantity of Cs of 10% in the structure CsxMA1-xPbI3 (Perovskite with superior phase durability), can be very promising for the realization of efficient Perovskite type solar cells.